Aim small, miss small: To what extent does it work? - Christina, B.; Alpenfels, E. (International Journal of Golf Science, 2019)
The effectiveness of the "Aim Small, Miss Small" method was studied for golf performance (92 adult males) involving drives (driver, three-metal), full iron shots (nine, six iron), and short-game shots (putting, chipping, pitching). Aiming at a larger target resulted in better average driver driving accuracy with longer average total distance, and longer average carry distance for both irons without sacrificing any accuracy. These driver and iron performance findings indicated that it was more beneficial to aim at a large rather than small target, which is counter to what the "Aim Small, Miss Small" method predicts. Also counter to what the method predicts was the finding that average accuracy of the three-metal, nine and six irons, putts, chips and pitches was unaffected by the target size at which participants aimed. Thus, no evidence was found to support the belief in superior effectiveness of the "Aim Small, Miss Small" method.